Tabaquismo en adolescentes escolarizados en el municipio de Filadelfia (Colombia): prevalencia y variables asociadas - Estrada López, María Yeraldin; López Cárdenas, Johanna Paola; Puello Ávila, Antonio Carlos (Cultura del cuidado, 2012)
Objective To determine the prevalence of smoking and associated variables in students from middle and high school from educational institutions in the town of Filadelfia (Colombia). Methodology A descriptive, cross-sectional study was conducted. The subjects were students between 10 and 19 years old. A sample of 360 students was calculated. These were selected under a scheme of sampling by bietápico cluster with a random selection of proportional probabilities related to the size of the cluster. The global survey of smoking for young students was used. Results A participation of 313 students was obtained. The group that had greater participation was sixth grade with 27,5%. The age of the participants had a media of 13,8 years (SD ± 2); the gender distribution corresponded to 51,4% male (n = 161) and female of 48,5% (n = 152). The lifetime prevalence of cigarette consumption was 28,0% lC 95% (18,8 - 36,5). The logistic regression analysis showed an association with smokers in other places, with alcohol consumption, and the use of psychoactive substances. Recomendation The Department of Health of the municipiality should design prevention programs for adoslecents who have not started smoking, and programs to di who currently do it, making emphasis on those who smoke on a daily basis.